Bipolar disorder - Strakowski, Stephen M.; DelBello, Melissa P.; Adler, Caleb M.; Fleck, David E. (New York : Oxford University Press, 2020)
Bipolar disorder is among the most common conditions affecting humankind and one of the leading causes of disability worldwide. It is a complex and dynamic psychiatric condition that makes it difficult to both understand and manage. However, with good management, people affected by bipolar disorder can lead very successful lives. This book was written specifically with new psychiatrists and mental health practitioners in mind to facilitate their ability to care for this condition. Chapters review clinical presentation and epidemiology, etiology and neurobiology, and treatment of bipolar disorder.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 11, 2020).
Keywords: Manic-depressive illness; Manic-depressive illness -- Treatment